Disconnection In Language Disorders - Shanbhogue K.R; Bijoy-Menon K; Mugunthan K; Balasubramania S; Gopinathan S; Natarajan V (Annals of Indian Academy of Neurology, 2005)
Disconnection can be a pathophysiological mechanism in language disorders. We report three cases where disconnection is postulated as a causative factor for the aphasic syndromes. These are alexia without agraphia, conduction aphasia and aphasia. The pathophysiology is discussed and the :neural network" theory of brain function highlighted.